METODE DAKWAH INFLTRASI: SPIRIT KESETARAAN GENDER DALAM KONTRUKSI KARAKTER SRIKANDI - Ahmad Hidayatullah; Izza Himawanti (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2021)
Glorifying women and preventing them from all kinds of discrimination is an integral part of Islam. Therefore this spirit has always been instilled from generation to generation as evidence of the truth of Islam rahmatan lil alamin. The inconsistency between values and reality on the ground is caused by certain people who destroy the concept. Meanwhile in Indonesia, Walisongo as the representative of the most successful spreaders of Islam in the history of preaching the archipelago has also done the same thing. It's just that the patriarchal culture that was still attached to Javanese society in that era made Walisongo more refined in instilling this spirit with the method of preaching infiltration, in order to avoid resistance and even conflict in the community. In the end, wayang was chosen as a medium for implementing the method, through the construction of the Srikandi character. Using this type of qualitative research with a sociological historical analysis approach, this research tries to explore how the implementation of the dakwah infiltration method through the construction of Srikandi characters so that it can accommodate issues of gender equality. As for the results of this study, it can be concluded that the implementation of the infiltration da'wah method is carried out by constructing the Srikandi character so that it has a striking difference from its original form - the Hindu Mahabharata version -. In his new form, Srikandi is depicted as a real woman who becomes Arjuna's wife, symbolizing the emancipation of women without having to leave their nature as a woman.).